Ring width chronolgies (N=91) from the three boreal forest tree species and shrub (alder) across a bioclimatic gradient in western Alaska at the lower Seward Peninsula sampled in 2024 - Stefan Kruse; Fenja Sevke; Nelly Zens; Alexander Baake; Léa Enguehard (PANGAEA, 2025)
The data set consists of tree ring width chronologies from tree species. The samples were taken with an increment borer predominantly from the north of the tree at breast height (1.3 m above ground) and were dried in the field. In Potsdam, we sanded, digitized and further processed the scans by identifying the ring layers (from bark to pith and including or estimating the centre) and exporting the tree ring width for each year in one data file. By crossdating we checked against other tree ring width chronologies from the same site for missing rings and corrected them. The data containing files in dendrochronological TUCSON format (1/100 mm) are added in the Metadata-section as "other version". The region covered is part of the Northern Boreal Forest and the Tundra-Taiga Ecotone (TTE). The fieldwork was planned and carried out by researchers from the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the University of Alaska Fairbanks (UAF). It took place in the summer of 2024, from 18 June to 17 July. The study area covers boreal forests in different bio-climatic regions and revisits sites established in 2023 and adds more sites. Additionally, the Tundra-Taiga Ecotone was sampled at the Seward Peninsula from the westernmost forests in Alaska close to the settlement of Council and towards Nome.